Integration and 'mandata': the Roman provincial administration in the correspondence between Pliny the Younger and Trajan - Costa, Alex Aparecido da; Venturini, Renata Lopes Biazotto (Romanitas - Revista de Estudos Grecolatinos, 2017)
The administration of the Roman provinces did not obey a pre-established legislation, being based on instructions, mandata, of the Caesars to the governors. Therefore, the purpose of this article is to propose an analysis about the instructions present in the correspondence between Trajan and Pliny the Younger concerning the government of Bithynia, from the concept of integration in the Roman Empire.
Keywords: Roman Empire; Administration; Province